Short report on the archeological investigations of the City of Austin's proposed Boggy Creek bikeway improvements in Travis County, Texas - Haefner, Josh; Fulmer, John (Hicks & Company Archeology, 2012)
This report provides information on the 100 percent intensive linear archeological survey for the proposed City of Austin's Boggy Creek Bikeway Improvements project located in Travis County, Texas.